Ensuring emergency planning & response meet the minimum Process Safety Management (PSM) standards requirements - Abdul Majid, N.D. (Elsevier Ltd, 2016)
When incidents happen and the consequences are not mitigated effectively, one of the indicated failures consists of ineffective emergency planning and response (EPR). EPR is an important aspect of the Process Safety Management (PSM) Standards, and the guidelines are stated in CFR 1910.119 (n) which explains the minimum elements of emergency response and procedures in handling emergency or small releases. Despite its implementation in 1992, CSB finds ineffective EPR system in certain accidents such as the Missouri DPS Enterprise Chlorine Gas Release accident in 2002. DPS EPR failed in planning on location of emergency equipment and accessibility. Many other accidents have occurred throughout the decade and even though organizations have their own EPR system, there are issues in meeting minimum PSM requirements. There also exists the problem of self-regulatory policies practiced by organizations, which might not meet these requirements as well. To help organizations meet these minimum requirements, the purpose of this paper is to present a structured and easy technique to plan and implement EPR as per PSM requirements. A model has been developed based on this technique, and its application has been tested as a case study in a refinery in Malaysia and discussed throughout this report. The results reflected the feasibility of this model as it helped users to track and manage documents efficiently. This technique has the potential to help users to manage EPR better and to reduce adverse impacts to people, environment and assets. Â© 2016 Elsevier Ltd.